(untitled) (Simbiótica. Revista Eletrônica, 2023)
The Semantic Fields Model is a proposal presented by Rômulo Lins as a methodological model and a theory of knowledge. The MCS intends to explain how meanings are produced for objects. As the production of meaning is a traditional debate in many areas, we were interested in understanding the foundations of MCS in dialogue with Wittgenstein’s philosophy, especially in its second phase, due to the theoretical improvement achieved with its maturity. In terms of research material, texts by Rômulo Lins and Wittgenstein’s two main works – the Tractatus Lógico-Philosophicus and the Philosophical Investigations – constitute the basis, in addition to the contribution of secondary readings about their work. In the findings we have elements of approximation and discussion of nuances that allow us to affirm the scope of our objective.